Killing it - Bockoven, Mike (Polis Books, 2023)
Since the late 1980's, The Square had been one of the most important clubs in New York for the alt-comedy scene. But before that it was something much darker and is now a place where evil lingers, waiting for a chance to spill blood. After a night of killing on stage, four comics find themselves in a desperate situation as the spirits of the past come out to play, and a fight for laughs becomes a fight for survival in the most unlikely of places.